Mula sa liwanag ay pag-asa: A history of lighthouse bible baptist church from 1976-2021 - Doller, Tisha Noleen H. (Animo Repository, 2024)
This study is about the development of the Lighthouse Bible Baptist Church through its institutional history from 1976 to 2021. The roots of its growth can be traced back from the church’s adherence to the biblical practices of the New Testament Churches which was learned from the Bible Baptist Church of Sociego managed by American Baptist Missionaries during the post-World War II and the teachings were then applied by the founder Rev. Bienvenido Abante Sr. of Lighthouse Bible Baptist Church during its establishment in 1976. The goal of the New Testament Churches is espoused by the idea of the “Social Gospel” or the way of doing missions through “Preaching, Teaching, and Healing”. With the transfer of leadership to Bishop Reuben Abante in 1999 this was further manifested through church planting, the establishment of schools, and medical missions. In 2021 the church celebrated its 45th anniversary with the theme Edified and Fortified at 45! that aligns with the theme of the National Baptist Day Law to “Educate, Evangelize, and Equip” which aims to recognize what makes the Baptist Churches in the Philippines distinct among all the church denominations since the arrival of the first Baptists in May 3, 1900. This study is further grounded by the New Institutionalism Theory to analyze how the church community interacts with similar institutions as they uphold their beliefs, teachings, and practices in contributing to Philippine society. The descriptive-analytic and oral history methodologies will be utilized in creating the historical narrative.